Deconstruction and fractalization of urban identity - mojtaba Valibeigi (Journal of Urban Society's Arts, 2020)
The research, by referring to the Dur Untash city at the Symbolic level, seeks to answer the question that how in urban semiotics, the city's identity has acquired a semantic significance beyond its significance. The situation of the city expresses a state that any kind of dominant discourses has lost their accreditation capacity and authority, and the audience cannot rely on any of the currents that were considered as definitive. City identity is nothing but fractal games that there is no source of authority that indicates the fixed meaning of these formulas and this is a social contract. These contracts derive from the semiotic rules which is agreed upon in the community. In this game will be try to impose certain meanings on the city identity using the symbolic function; to internalize meta-narrative (internalization process) and in this way, the identity and the presence of the Dur-Untash city will be recorded in time and reach an immortal realm.